Distributed generation with parallel connected inverter - Younis, U.A.A.; Rahirn, N.A.; Mekhilef, Saad (2009)
This paper presents the design and analysis of a new configuration of parallel connected inverter suitable for Distributed Generation Application. The configuration consists of dc/dc converter and parallel three-phase dc/ac inverter. Series resistors added to the inverter output to maintain same current in each inverter of the two parallel inverters, and to reduce the circulating current in the parallel inverters to the minimum. Third harmonic injection PWM (THIPWM) reduces the total harmonic distortion and to make maximum use of the voltage source. DSP was used to generate the THIPWM and the control algorithm for the converter. PID controller is applied on the full-bridge dc/dc converter side to maintain the ac voltage to the required level. Selected experimental results have been shown to validate the proposed system.